Wide Area 2D/3D Imaging Development, Analysis and Applications - Langmann, Benjamin; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2014)
Imaging technology is an important research area and it is widely utilized in a growing number of disciplines ranging from gaming, robotics and automation to medicine. In the last decade 3D imaging became popular mainly driven by the introduction of novel 3D cameras and measuring devices. These cameras are usually limited to indoor scenes with relatively low distances. Benjamin Langmann introduces medium and long-range 2D/3D cameras to overcome these limitations. He reports measurement results for these devices and studies their characteristic behavior. In order to facilitate the application of these cameras, common algorithms are adapted to the 2D/3D data and new approaches for standard computer vision tasks are introduced. Contents Long-Range 2D/3D Imaging Fundamentals of Time-of-Flight Cameras 2D/3D Camera Calibration Background Subtraction, Segmentation and Tracking Target Groups Graduate students and scientists of computer sciences and engineering Engineers in research and development of safety engineering and automation technology The Author Benjamin Langmann studied computer science and mathematics at the Technical University of Braunschweig, received a doctorate degree from the University of Siegen and leads now the research group (3z(BIndustrial and Medical Imaging(3y (Bat the Institute for Measurement and Automatic Control of the Leibniz University Hannover, Germany.s
Introduction -- Depth Camera Assessment -- PMD Imaging -- Calibration of Depth Cameras -- Multi-Modal Background Subtraction -- Super-Resolution for Depth Maps -- Multiple Camera 2D/3D Tracking -- Conclusion.
Keywords: Computer science; Computer graphics; Control engineering; Robotics; Mechatronics; Industrial engineering; Production engineering; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Control, Robotics, Mechatronics; Industrial and Production Engineering; Electronic books